Implementing Leadership Style to Improve Organizational Performance Mediated by Organizational Identification - Sentoso, Antony; Jeffry, Jeffry; Mon, Muhammad Donal (Almana : Jurnal Manajemen dan Bisnis, 2024)
Before the progress of the times and technology that was increasingly developing and rapidly as well as intense business competition, experts highlighted the important role of performance in organizations to improve the sustainability of life based on the promotion of leadership styles. This research aims to provide additional information on companies operating in the distributor sector in implementing leadership styles to improve organizational performance. This research uses quantitative methods. The population in this study was 261 workers in the distributor industry in Batam City. All research has met the criteria for validity and reliability. The results of the research state that Innovative leadership significantly affects both organizational performance and organizational identification, but not when organizational identification acts as a mediating factor. Second, organizational performance and identification are not significantly impacted by transformational leadership. The same holds if organizational identity acts as a mediator. It was discovered that organizational identity significantly affects organizational performance and that strategic leadership styles do not significantly affect organizational performance. Thus, it can be said that while leadership style has a significant impact on organizational performance, not all leadership philosophies are appropriate for usage in a given setting.